Efektivitas Kemasan Standing Pouch Pasta Bawang Merah pada Penyimpanan Suhu Beku dan Suhu Ruang - Tantalu , Lorine ; Isrofatin; Bano, Isabella Gracela ; Kaka , Yohana Depa (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
One of the most popular processed red onion alternatives is the shallot paste. As part of an intermediate product, it serves core spices from natural onions and ready to use. This study aims to obtain quality shallot paste in standing pouch packaging for freezing and room temperature storage through Total Plate Count (TPC), Total Acid and Water Content calculation and analysis of the product. In the preliminary test, the Extended Storage Studies (ESS) method was used to determine the feasibility of shelf life. The research method used is the standing pouch paste onion stored for 0, 4, 8, 12 days at room temperature and freezing temperature. The results of the ESS method showed that storage with freezing temperatures provided quality that did not change until storage was over 12 days, supported by the calculation of TPC 18 x 103 CFU / g which was still below the SNI threshold. Depletion of water content during storage of room temperature (86.81-81.5%) and freezing temperature (85.75-81.66%) and increase in Total Acid 11% of each storage temperature.